Navigating productivity dilemmas and conflicting loyalties in activity-based flexible offices - A qualitative study of managers’ perspectives and coping strategies - Maral Babapour Chafi; Maria Nordin; Viktoria Wahlström; Anita Pettersson-Strömbäck (PLoS ONE, 2025)
Activity-based Flexible Offices (AFOs) provide employees with a variety of workspaces to choose from based on their tasks, rather than having assigned desks. While the adoption of AFOs is increasing due to flexibility and cost-efficiency, there is limited research about the consequences of transitioning to AFOs from the perspective of staff managers. The purpose of this study is to explore how managers experience and cope with challenges that may arise in AFOs. Our qualitative descriptive study is based on two case studies that investigate the consequences of AFOs. Data collection involved semi-structured interviews with a total of 33 managers in two organisations, 12–18 months post-relocation. An inductive, bottom-up process was used for coding and thematization of the interview transcripts. Our results show that AFOs can enhance communication and collaboration depending on the units’ collaboration needs and prior geographical distribution. However, this effect was overshadowed by task-environment misalignments on within-team communication, distractions, and limitations on adjustments and recruitments. Additionally, managers faced conflicting loyalties between defending the organisation’s decision to implement AFOs while ensuring compliance with legal work environment requirements despite limited resources. There is a risk that the implementation of flexible offices will fragment and complicate managers’ tasks, such as ensuring that daily operations run smoothly, meeting legal responsibilities, and managing and recruiting staff. This poses a risk to managers’ productivity and health, and consequently, the achievement of organisational goals. The study uncovers managerial experiences, challenges, and coping strategies in AFOs, offering valuable insights for organisations considering this office type.